The use of the subsidy dependence index technique in appraising the performance of a rural financial intermediary : a case study of the Kwazulu finance and investment corporation - Coetzee, G.K. (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Agricultural Economics))--University of Pretoria, 2007.